Influencia de la psicomotricidad, en la escritura del sistema braille de los niños con discapacidad visual de la escuela especializada Byron Eguiguren. Periodo 2019-2020. Propuesta Psicopedagógica - Sánchez Ríos, María Virginia (2021)
In the present investigation, a compendium of information was carried out according to the study variables, these being psychomotor skills and the Braille System in order to improve the reading and writing in Braille of children with visual disabilities, for this the design of the investigation is of descriptive, bibliographical, argumentative, expository and purposeful nature. Its general objective is to carry out a bibliographic research regarding the influence of Psychomotor skills, aimed at facilitating the writing of the Braille System of children with visual disabilities, the collection of information was done through a sample of: 25 journal articles, 15 books, 9 web pages, 10 theses, 4 documents and 1 interview, having a total of 64 bibliographic sources, thus developing a psychopedagogical proposal based on the stimulation of psychomotor skills, proposing a series of adapted psychomotor exercises, which can be applied both in a center educational just like home. Finally, as the main conclusion, it was specified that psychomotor skills help the performance of reading and writing in Braille, since it provides development and muscular and mental stimulation, therefore, when performing psychomotor exercises, activities that are relevant to the area to be stimulated should be chosen; Regarding the recommendations, the importance of making an initial diagnosis of the child with visual impairment is highlighted in order to know the most affected psychomotor areas and thus choose the activities that are most fruitful for the child's psychomotor development and can improve their reading and writing in Braille.